Green Self-Identity as a Mediating Variable of Green Knowledge and Green Purchase Behavior - Yunita Budi Rahayu Silintowe; I Made Sukresna (LPPM Universitas Terbuka, 2022)
Purpose - Most environmental problems can be solved with community support through public purchase behavior on eco-friendly products. Therefore, this study aimed to examine the effect of green knowledge on purchase behavior with self-identity as a mediating variable. Methodology - The data were collected using a questionnaire and a self-administered survey, generating 271 valid responses. The PLS-SEM approach with SmartPLS Version 3.0 was used to develop a study model and evaluate hypotheses. Findings - The results showed that green knowledge influences purchase behavior and self-identity. Furthermore, green self-identity influences purchase behavior and mediates between knowledge and purchase behavior. When customers gain more knowledge, their identity in caring for the environment increases and enhance the purchase behavior of eco-friendly products. The results implied that business people should educate consumers concerning environmental conservation efforts through the use of eco-friendly products. Originality - Green self-identity as a mediator between green knowledge and purchase behavior. Studies on green self-identity are still limited as many focus on purchase intention in green products, only a few studies focus directly on green purchase behavior.